2022
DOI: 10.3390/coatings12111774
|View full text |Cite
|
Sign up to set email alerts
|

Bi2O3-Assisted Sintering of Na3Zr2Si2PO12 Electrolyte for Solid-State Sodium Metal Batteries

Abstract: Solid-state sodium metal batteries using non-flammable solid-state electrolytes are recognized as next-generation energy storage technology in view of their merits of high safety and low cost. However, the lower ion conductivity (below the application requirements of 10−3 S cm−1) and interface issues that exist in electrolytes/electrodes for most solid-state electrolytes hinder their practical application. In this paper, NASICON-type Na3Zr2Si2PO12 (NZSP) electrolytes with enhanced ion conductivity are synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It is worth noting that the remaining sintering aids may also have a beneficial effect on the sintering process. [19][20][21][22][23][24] Certainly, this method is not limited to the NZSP material system, but also can be extended to the other kinds of oxides system, such as Li Figure 2a,b show the XRD patterns of NZSP-NBO sintered at 1100 °C (NZSP-NBO-1100 °C). The main diffraction peaks of samples coincide well with the monoclinic structure of Na 3 Zr 2 Si 2 PO 12 (PDF#: 84-1200).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worth noting that the remaining sintering aids may also have a beneficial effect on the sintering process. [19][20][21][22][23][24] Certainly, this method is not limited to the NZSP material system, but also can be extended to the other kinds of oxides system, such as Li Figure 2a,b show the XRD patterns of NZSP-NBO sintered at 1100 °C (NZSP-NBO-1100 °C). The main diffraction peaks of samples coincide well with the monoclinic structure of Na 3 Zr 2 Si 2 PO 12 (PDF#: 84-1200).…”
Section: Resultsmentioning
confidence: 99%
“…[36] The E a of NZSP-7%NBO-1100 °C, NZSP-3%NaF-1150 °C, and NZSP-3%CuO-1100 °C is 0.24, 0.23, and 0.24 eV, respectively, which are pretty lower in comparison with these recently related reports (Table S2, Supporting Information). [5,24,29,37,38] Figure 7a shows the EIS plots of bare NZSP-1200 °C, NZSP-7%NBO-1100 °C, NZSP-3%NaF-1150 °C, and NZSP-3%CuO-1100 °C ceramic electrolytes-based symmetric sodium metal cells. In general, the sintering aids modified NZSP electrolytes-based symmetric cells show smaller impedance than that of the Na/NZSP/Na cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, usually, related equipment is expensive and not suitable for large-scale production. In addition, the sintering aids, such as CuO, NaPO 3 , Na 2 SiO 3 , Bi 2 O 3 , Na 2 BO 3 , B 2 O 3 , and NaF, are employed to accelerate the uniform growth of grain and realize the densification sintering of ceramic electrolytes at a relatively low temperature. Our previous research reported that the densification sintering of the Na 3 Zr 2 Si 2 PO 12 ceramic and the sodium ion transfer capability across the grain boundary were facilitated by using Na 2 B 4 O 7 as a sintering aid . In the meantime, the area-specific resistance of Na/Na 3 Zr 2 Si 2 PO 12 -10 wt %Na 2 B 4 O 7 (36 Ω cm 2 ) is observably lower than that of Na/Na 3 Zr 2 Si 2 PO 12 (90 Ω cm 2 ).…”
Section: Introductionmentioning
confidence: 99%